Nominal and real stochastic convergence within transition economies and to the European Union: Evidence from panel data - Ali M. Kutan; Taner M. Yigit (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2002)
This paper investigates the issue of real and nominal economic convergence of transition economies in two distinct ways: i) within their own groups as in Koèenda (2001) and ii) to the European Union (EU). We extend Koèenda's study not only by using a more stable period (post-93) but also by employing a more recent panel estimation approach developed by Im, Pesaran, and Shin (IPS) (1997), which offers less restrictive assumptions about convergence by allowing heterogeneity in the convergence rates than previous panel unit root techniques. Relaxing the assumption of homogeneity in convergence rates yields less convergence in price level and money supply variables than reported by Koèenda. Again using the IPS method, we extend the investigation to examine the convergence of the first and second round candidate economies to EU standards. We find that the first-round candidates have made significant progress in monetary policy convergence with respect to EU and there is significant real convergence between the first round candidate economies and EU, but not for the second round candidate countries. The results have important implications for full EU membership preparations by these countries, including the choice of an optimal interim exchange rate policy.
Keywords: 330